TO STUDY THE EFFECT OF MATERNAL FACTORS ON MORTALITY OF VERY LOW BIRTH WEIGHT NEONATES - HARINKHEDE, ANITA; KUMAR PATEL, DEEPAK; NAGWANSHI, JYOTI; RAHANGDALE, AMIT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The present study is to determine the influences of maternal risk factors on neonatal mortality in very low birth weight (VLBW) infants born in central India. Methods: A nested case–control study was conducted in the prospectively assembled cohort at the Department of Pediatrics Government Medical College and Hospital, Nagpur, India, for 2 years. Intramural neonates admitted to NICU with a birth weight of 500–1500 g were included in the study. Newborns with major congenital malformation and those who died in the delivery room or within 12 h of birth were excluded from the study. Results: A total of 260 inborn VLBW newborns admitted to the NICU were enrolled. The mean gestational age was 33.58±4.8 weeks, and the mean birth weight was 1256.56±182.8 g. The overall case fatality rate was 50.38%. Maternal body mass index (BMI) <18.5 g/m2 (p=0.0019 [(Odds Ratio [OR]=3.23) (95% confidence interval [CI]. 1.43–7.80)]) and ante partum hemorrhage (p=0.0001[(OR=3.57) (95% CI 1.82–7.22)]) were two maternal factors which significantly increased the risk of death. However, antenatal steroid coverage (p=0.0005 [(OR=2.25) (95% CI 1.12–5.35)]) was associated with improved survival of VLBW neonates. Conclusion: It can be said that very low birth neonates, especially those weighing <1000 g, preterm, and who are critically ill due to disturbance in pulmonary and circulatory physiology have a very high risk of mortality. Low maternal BMI and antepartum hemorrhage in mothers of VLBW neonate were associated with increased neonatal mortality and ACS therapy was associated with decreased neonatal mortality.